2017
DOI: 10.3390/ma10070733
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Damage of the Head-Neck Junction in Hard-on-Hard Total Hip Replacements: Effect of Femoral Head Size, Metal Combination, and 12/14 Taper Design

Abstract: Recently, concerns have been raised about the potential effect of head-neck junction damage products at the local and systemic levels. Factors that may affect this damage process have not been fully established yet. This study investigated the possible correlations among head-neck junction damage level, implant design, material combination, and patient characteristics. Head-neck junctions of 148 retrieved implants were analysed, including both ceramic-on-ceramic (N = 61) and metal-on-metal (N = 87) bearings. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 78 publications
2
5
0
Order By: Relevance
“…Interestingly, minimal cobalt was found in the corrosion particles on the implant surfaces (Mathiesen et al, 1991; Urban et al, 1997). These observations were later confirmed by other researchers (Huber et al, 2009; Chana et al, 2012; Baleani et al, 2017). The Cr-rich fretting corrosion products with low or depleted Co indicated that Co was released in the form of soluble species.…”
Section: Mechanisms Of Implant Degradationsupporting
confidence: 73%
“…Interestingly, minimal cobalt was found in the corrosion particles on the implant surfaces (Mathiesen et al, 1991; Urban et al, 1997). These observations were later confirmed by other researchers (Huber et al, 2009; Chana et al, 2012; Baleani et al, 2017). The Cr-rich fretting corrosion products with low or depleted Co indicated that Co was released in the form of soluble species.…”
Section: Mechanisms Of Implant Degradationsupporting
confidence: 73%
“…Evidence supporting the proposed mode of failure can be found in the literature. Analysis of retrieved ceramic heads and male tapers has revealed that some minor damage, mainly localized damage to the ridges of the taper machining grooves associated with light metal transfer to the bore surface, takes place in well-working bore–taper junctions [ 26 , 27 ]. However, suboptimal seating increases both contact pressure and micromotion amplitude at the bore–taper interface under physiological load [ 28 ], thus promoting fretting-corrosion damage of the taper [ 29 , 30 ] and crack nucleation at the ceramic surface [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to material dimensions restrictions, in this case, a 12 mm diameter rod, it was not possible to obtain a cone with real dimensions of the most used geometries in total hip arthroplasty. [26][27][28][29][30] Therefore, the 6°Ca angle was chosen equal to the 12/14 type cone, in which the 12 mm dimension corresponds to the Dcd.…”
Section: Methodsmentioning
confidence: 99%